Availability and Nutritional Composition of Street Food in Urban Central Asia: Findings From Almaty, Kazakhstan - Albuquerque, G (2022)
Objective: To describe the availability and nutritional composition of commonly available street foods in Almaty, Kazakhstan. Methods: 384 street food vending sites (in 10 public markets) were assessed; information on vending sites characteristics and food availability and samples of the most commonly available street foods (81 homemade; 40 industrial) were collected for chemical analysis. Results: Fruit, beverages and food other than fruit were available in 1.0%, 47.4% and 92.7% of all vending sites. Homemade food other than fruit (e.g., bread, main dishes, snacks, pastries, sandwiches, and cakes) were available in 63.4% of stationary vending sites, while industrial (e.g., snacks, chocolate, cakes, and cookies) in 45.6% of them. Industrial foods were the most energy-dense [median kcal/100 g: 438.8 vs. 267.2, p < 0.001 (homemade)]. Traditional homemade dishes were high in sodium, reaching 2,248 mg/serving (lagman) and major contributors of protein and fat to energy content (shashlik: 22.8% from protein, 68.3% from fat). Industrial chocolate and homemade cake presented the highest saturated (14.6 g/serving) and trans-fat (3.20 g/serving) contents. Conclusion: These findings advocate for the implementation of health promotion strategies targeted at vendors, consumers and other stakeholders. Copyright (c) 2022 Albuquerque, Lança de Morais, Gelormini, Sousa, Casal, Pinho, Damasceno, Moreira, Breda, Lunet and Padrão.